2011
DOI: 10.1148/radiol.10100995
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Contrast-enhanced MR Imaging Measurement of Vertebral Bone Marrow Perfusion May Be Indicator of Outcome of Acute Myeloid Leukemia Patients in Remission

Abstract: Bone marrow perfusion measured with DCE MR imaging in AML patients in CR can be an indicator of outcome and survival. K(ep) measured with kinetic modeling was useful and significantly associated with RFS, while heuristic parameters (peak and slope) were not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…For example, the universally over-expressed WT1 antigen in AML has been used successfully to determine chemosensitive disease using a PCR approach [27]. Similarly, the use of dynamic contrast enhanced magnetic resonance imaging (DCE-MRI) to measure changes in bone marrow microvascular density as an indicator of active disease, has been effectively employed as a noninvasive interim monitoring tool [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the universally over-expressed WT1 antigen in AML has been used successfully to determine chemosensitive disease using a PCR approach [27]. Similarly, the use of dynamic contrast enhanced magnetic resonance imaging (DCE-MRI) to measure changes in bone marrow microvascular density as an indicator of active disease, has been effectively employed as a noninvasive interim monitoring tool [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Also, several studies have applied DCE-MRI to monitor treatment-induced changes using different therapies, for example, chemotherapy (17), radiation therapy (20), angiogenic therapy (19), and stem cell transplantation (16). DCE-MRI parameters have been shown to be associated with prognosis and survival of patients, which might be related to the angiogenesis of the disease (1418,33). It was found that a higher microvessel density was correlated with higher tumor grade, worse prognosis, and shorter survival in myeloma patients (34–36).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the risks of a contrast (gadolinium) toxicity is lower than with CT scans. Recently, two groups have shown early data that dynamic contrast enhanced- (DCE-) MRI can be used to assess bone marrow vascular perfusion and predict for response to chemotherapy [51, 52]. …”
Section: Summary and Future Directionsmentioning
confidence: 99%